How Do I-Deals Influence Client Satisfaction? The Role of Exhaustion, Collective Commitment, and Age Diversity. (April 2019) - Bal, P. Matthijs; Boehm, Stephan A.
This paper introduces a multilevel perspective on the relationships of idiosyncratic deals (i-deals) with organizational outcomes (i.e., client satisfaction) and investigates how and under which conditions these relationships manifest. On the basis of contagion theory, we proposed that the positive effects of i-deals will spill over within organizational units (indicated by reduced emotional exhaustion and enhanced collective commitment), which leads to increased customer satisfaction. Moreover, we postulated that the effects of i-deals would be more prominent in units with high age diversity, as i-deals are more important in units where people's work-related needs are more heterogeneous due to the higher diversity in employee age. A study among 19, 780 employees and 17, 500 clients of a German public service organization showed support for the contagion model and that i-deals were negatively related to individual emotional exhaustion and subsequently positively related to collective commitment within units and client satisfaction measured 6 months later. Emotional exhaustion and collective commitment mediated the relationships between i-deals and client satisfaction. Finally, we found that the relationships between i-deals and emotional exhaustion / client satisfaction were more strongly negative in units with high age diversity, rather than in units with low age diversity, indicating the benefits of i-deals within units with high age diversity to reduce emotional exhaustion and enhance client satisfaction.